PELATIHAN PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) UNTUK MENDUKUNG PEREKONOMIAN BERKELANJUTAN DI DESA UNGASAN - I Made Sujana; Fahmi Tanjung; Putu Ratna Windusara Putri; I Made Wisnu Wardana (Nusantara Hasana Journal, 2022)
Village-Owned Enterprises (BUMDes) serve as strategic instruments in promoting rural economic growth and improving community welfare through the productive management of local resources. However, many BUMDes continue to face challenges related to business management, organizational governance, financial administration, and sustainable business development. Ungasan Village, located in Badung Regency, possesses significant economic potential, yet the optimization of BUMDes functions still requires strengthening human resource capacities. This community service program aimed to enhance the competencies of BUMDes managers in organizational management, financial administration, business planning, and local potential-based business development strategies. The methods employed included socialization, training, mentoring, case studies, and program evaluation. A total of 35 participants consisting of BUMDes administrators, village officials, and community representatives attended the program. The results indicated significant improvements in participants’ understanding of BUMDes governance, financial reporting, business planning, and village business development strategies. Furthermore, participants successfully developed systematic business development plans oriented toward sustainable rural economic growth. The program contributed positively to strengthening institutional capacities and enhancing the role of BUMDes as a driver of sustainable village economic development.